Occupational Exposure to Engine Exhausts and Prostate Cancer Risk - Christine Barul; Marie-Claude Rousseau; Marie-Elise Parent (Environmental Health)
Abstract Background Some engine exhausts (EEs) have been classified as carcinogens and/or can have hormone-modulating properties that could play a role in prostate cancer development. Objective We investigated associations between lifetime occupational exposure to various EEs and prostate cancer risk, overall and for aggressive cancers. Methods In a population-based case–control study conducted in Montreal, Canada, 1,924 incident histologically-confirmed prostate cancer cases (436 aggressive) and 1,989 population controls were recruited. Socio-demographics, lifestyle factors and a detailed occupational history were collected during in-person interviews. Industrial hygienists conducted evaluations of intensity, frequency and reliability of exposure to EEs resulting from the combustion of several fuels (any diesel, light- and heavy-duty diesel, leaded and unleaded gasoline, propane and jet fuel) in each job held ≥ 2 years. Odds ratios (ORs) and 95% confidence intervals (CI) were estimated for exposure to each EE, in association with prostate cancer risk, adjusting for age and then for potential lifestyle and occupational confounders, accounting for a 5-year latency period. As most associations were not linear, we fitted functions for changes in percentile distributions based on natural cubic splines. Results There was no evidence of associations between exposure to the various EEs and overall prostate cancer. However, for high-grade cancers, based on the fully-adjusted model, a change from the 25th to the 75th percentile of the exposure distribution of any diesel EE yielded an OR of 1.24 (95%CI 0.96–1.61), and of 1.27 (95% CI 0.80–2.01) for a change from the 75th to the 95th percentile. These increases reflected exposure to diesel EE from light-duty vehicles, associated with similar ORs. For leaded gasoline EE, a change from the 75th to the 95th percentile resulted in an age-adjusted OR of 1.36 (95%CI 0.88–2.11), which was attenuated to 1.12 (95%CI 0.63–2.02) after full adjustment. There were no associations with EE from unleaded gasoline, diesel from heavy-duty vehicles, jet fuel and propane. Conclusion There was suggestive evidence for a deleterious role of occupational exposure to EE resulting from the combustion of any diesel, light-duty diesel and from leaded gasoline in the development of aggressive prostate cancer. Results were independent from prostate cancer screening patterns.